2006
DOI: 10.1525/jlin.2006.16.2.194
|View full text |Cite
|
Sign up to set email alerts
|

Little Women and Vital Champions: Gendered Language Shift in a Northern Italian Town

Abstract: The connection of language to class is clearly implicated in the language shift in progress in the northern Italian town of Bergamo. Gender also plays an active part in this shift in terms of linguistic practice and language ideology, as a gendering of languages is occurring such that the local vernacular, Bergamasco, is linked to men, and the national standard, Italian, to women. This article demonstrates that this gendering is one mechanism of language shift, as it impacts the linguistic division of labor ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 19 publications
0
14
0
1
Order By: Relevance
“…Where it exists, one of the more persistent explanations remains Trudgill's concept of "covert prestige," in which the non-standard variety has greater appeal to men due to its connotation of working-class male values. Recently, Cavanaugh (2006) found something comparable with regard to Italian versus Bergamasco in the city of Bergamo, where data have shown that 15-25% more men report speaking the non-standard language than women. During interviews, locals of both genders consistently associated Bergamasco -the language itself and its use -with masculine character traits.…”
Section: Discussionmentioning
confidence: 91%
“…Where it exists, one of the more persistent explanations remains Trudgill's concept of "covert prestige," in which the non-standard variety has greater appeal to men due to its connotation of working-class male values. Recently, Cavanaugh (2006) found something comparable with regard to Italian versus Bergamasco in the city of Bergamo, where data have shown that 15-25% more men report speaking the non-standard language than women. During interviews, locals of both genders consistently associated Bergamasco -the language itself and its use -with masculine character traits.…”
Section: Discussionmentioning
confidence: 91%
“…Studies of (regional) bilingualism (McDonald 1994, Cavanaugh 2006, Gal 1978, Mukherjee 2003, Zuercher 2009) have examined choices and uses of different varieties of languages by women and their significance for the community as well as for the larger society. Since in many cultures the mother is the primary caretaker of the infant (Cavanaugh 2006) she decides what language to speak to her children.…”
Section: Discussionmentioning
confidence: 99%
“…Since in many cultures the mother is the primary caretaker of the infant (Cavanaugh 2006) she decides what language to speak to her children. For this reason, when it comes to the preservation of the ethnic language, women are either conservative, and use the ethnic language as the main linguistic tool within the household and with their friends, or they are un-concerned with the preservation of their ethnic language and encourage the use of the host country's language within the household (Cavanaugh 2006, Khemlani 2003. In Wissembourg, France, the Turkish language of the immigrants is still alive within the household and the ethnic community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations